Copepods in the Stomach of a Nototheniid Fish,Trematomus borchgrevinki Fry at Syowa Station,Antarctica - Hoshiai, Takao; Tanimura, Atsushi (1981)
P(論文) Copepods in stomach contents of fry of a nototheniid fish, Trematomus borchgrevinki which were caught on September 6, 1970 were examined to acquire information on the winter populations of copepods in the sea covered with the fast ice near Syowa Station (69°00'S, 39°35'E), Antarctica. The stomach contents were composed of Ctenocalanus vanus, Stephus longipes, two unidentified calanoid species, Oithona similis, Oncaea curvata, a few unidentified harpacticoid species, nauplius of copepods and unidentified copepods. O. similis and copepod nauplius were dominant. The component species of the stomach contents resembled those of the samples collected by vertical hauls of a plankton net in late autumn and in early spring. However, the relative abundance of copepod species in the stomach contents differed from that in the net samples. This may be reasonably ascribed to possible food preference of fish. Therefore, it is possible to assume that the winter populations of copepods do not differ from the late autumn and early spring populations. departmental bulletin paper